2016
DOI: 10.1016/j.ijmultiphaseflow.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Settling velocity of small inertial particles in homogeneous isotropic turbulence from high-resolution DNS

Abstract: The gravitational settling velocity of small heavy particles in a three-dimensional turbulent flow remains a controversial topic. In a homogeneous turbulence of zero mean velocity, both enhanced settling velocity and reduced settling velocity have been reported relative to the still-fluid terminal velocity. Dominant mechanisms for enhanced settling include the preferential sweeping and particleparticle hydrodynamic interactions. The reduced settling could result from loitering (falling particles spend more tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
57
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 56 publications
10
57
1
Order By: Relevance
“…We only plot cases in which the mean vertical fluid velocity is smaller than 0.25W s , and in fact in most cases it is 0.01 − 0.05W s . The first observation from the plot is that the vast majority of cases display strong settling enhancement, especially for St η ≈ 1, which is consistent with most previous numerical (Wang & Maxey 1993;Bosse & Kleiser 2006;Dejoan & Monchaux 2013;Bec et al 2014a;Ireland et al 2016b;Rosa et al 2016) and experimental studies (Aliseda et al 2002;Yang & Shy 2003Good et al 2014). The amount of such increase is more remarkable, with the settling velocity being enhanced by a factor 2.6 for St η ≈ 1 − 2.…”
Section: Mean Settling Velocitysupporting
confidence: 88%
“…We only plot cases in which the mean vertical fluid velocity is smaller than 0.25W s , and in fact in most cases it is 0.01 − 0.05W s . The first observation from the plot is that the vast majority of cases display strong settling enhancement, especially for St η ≈ 1, which is consistent with most previous numerical (Wang & Maxey 1993;Bosse & Kleiser 2006;Dejoan & Monchaux 2013;Bec et al 2014a;Ireland et al 2016b;Rosa et al 2016) and experimental studies (Aliseda et al 2002;Yang & Shy 2003Good et al 2014). The amount of such increase is more remarkable, with the settling velocity being enhanced by a factor 2.6 for St η ≈ 1 − 2.…”
Section: Mean Settling Velocitysupporting
confidence: 88%
“…Good et al (2014) were only able to observe loitering in their DNS when either the horizontal motion of the particles was artificially eliminated, or else when a non-linear drag force was used for the particles. However, as discussed earlier, other studies such as Rosa et al (2016) have found only a small effect of non-linear drag on the particle settling speeds, and they did not observe loitering.…”
mentioning
confidence: 53%
“…Nevertheless, DNS studies have also come to conflicting conclusions concerning the role of non-linear drag on particle settling speeds in turbulence. Wang & Maxey (1993) studied the influence of a non-linear drag coefficient using DNS and found that its effect was to only slightly reduce the particle settling speeds compared to the linear drag case, with similar results in Rosa et al (2016). However, Good et al (2014) observed a significant reduction in the particle settling velocity compared with the linear drag case, in certain regimes of St, Sv.…”
mentioning
confidence: 78%
See 2 more Smart Citations